Televisión digital: Cambio tecnológico o tecnología para el cambio - Arias Carbajal, Gerardo (2008)
This article is about Peru’s firsts steps to digital television. It emphasizes the need to think and debate about what type of television we want for the future (without leaving out the technical side witch must be evaluated to have a standard for digital terrestrial television or DTT) and this way turn this technological change into a chance to update all of the Peruvian television industry. Having said that, it discusses what kind of impact would, high definition television and the multicasting system (both key components of digital television), have in our country.